Electrocatalytic water oxidation from a mixed linker MOF based on NU-1000 with an integrated ruthenium-based metallo-linker. Issue 10 (14th April 2022) - Howe, Andrew; Liseev, Timofey; Gil-Sepulcre, Marcos; Gimbert-Suriñach, Carolina; Benet-Buchholz, Jordi; Llobet, Antoni; Ott, Sascha
Abstract : Pyrene-mediated hole hopping transport to ruthenium-based catalysts in the MOF crystal interior results in active water oxidation electrocatalysts. Abstract : A novel tetratopic metallo-linker, [Ru(tda)(py(PhCOOH)2 )2 ], 1, (tda = 2, 2′:6′, 2′′-terpyridine-6, 6′′-dicarboxylate; py(PhCOOH)2 = (4, 4′-(pyridine-3, 5-diyl)dibenzoic acid), that is structurally based on one of the most active molecular water oxidation catalysts has been prepared and fully characterized, including single crystal X-ray diffraction. 1 bears geometric similarities to H4 TBAPy (H4 TBAPy = 4, 4′, 4′′, 4′′′-(pyrene-1, 3, 6, 8-tetrayl)tetrabenzoic acid), i.e. the native linker in NU-1000, which offers the possibility to synthesize NU-1000-Ru mixed linker MOFs solvothermally. Mixed linker MOF formation was demonstrated by powder X-ray diffraction (PXRD) and scanning electron microscopy (SEM), and Ru linker incorporation confirmed by FT-IR, energy-dispersive X-ray (EDX) spectroscopy and inductively coupled plasma optical emission spectroscopy (ICP-OES). It was found that the Ru contents in the final mixed linker MOFs correlate with the amount of Ru linker present during solvothermal synthesis, albeit not in a linear fashion. The cyclic voltammograms (CV) of the mixed linker MOFs are largely dominated by TBAPy-based oxidations with features attributed to 1 . Interestingly, Ru linkers near the crystal surface are oxidized directly by interfacial hole transfer form the electrode, while those in the crystal interior can be oxidized indirectly from oxidized TBAPy linkers at more anodic potential. Upon repeated scanning, the CVs show the appearance of new waves that arise from irreversible TBAPy oxidation, as well as from the activation of the Ru-based water oxidation catalyst. Of the materials prepared, the one with the highest Ru content, NU-1000-Ruhigh, was shown to catalyze the electrochemical oxidation of water to dioxygen. The Faradaic efficiency (FE) of the construct is 37%, due to water oxidation being accompanied by oxidative transformations of the TBAPy linkers. Despite the low FE, NU-1000-Ruhigh is still among the best MOF-based water oxidation catalysts, operating by a unique co-linker mediated hole-transport mechanism to supply oxidizing equivalents also to catalysts in the crystal interior.